K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

30 tháng 10 2021

a) \(\left(-5\right)\left(-5\right)\left(-5\right)\left(-5\right)\left(-5\right)=\left(-5\right)^5\)

b)\(\left(-2\right)\left(-2\right)\left(-2\right)\left(-3\right)\left(-3\right)\left(+3\right)=\left(-2\right)^3\cdot\left(-3\right)^2\cdot3=\left(-2\right)^3\cdot3^3\)

c) \(\left(-7\right)\cdot7\cdot5\cdot\left(-5\right)\left(-5\right)=\left(-7^2\right)\cdot\left(-5\right)^3\)

d) \(\left(-8\right)\left(-3\right)3\cdot125=\left(-2^3\right)\cdot\left(-3^2\right)\cdot5^3\)

e) \(27\cdot\left(-2\right)3\left(-7\right)\cdot49=3^4\cdot\left(-2\right)\cdot\left(-7^3\right)\)

30 tháng 10 2021

a: \(\left(-5\right)\cdot\left(-5\right)\cdot\left(-5\right)\cdot\left(-5\right)\cdot\left(-5\right)=\left(-5\right)^5\)

b: \(\left(-2\right)\cdot\left(-2\right)\cdot\left(-2\right)\cdot\left(-3\right)\cdot\left(-3\right)\cdot\left(+3\right)=\left(-2\right)^3\cdot3^3\)

29 tháng 10 2023

126 = 2.32.7

 126 = 21.32.71

⇒ a = 1; b = 2; c = 1

Vậy a + b + c = 1 + 2 + 1 = 4

 

13 tháng 9 2017

đơn giản

21 tháng 10 2015

\(a,\left(-7\right)^6\)
\(b,\left(-4\right)^3.\left(-5\right)^3=\left[\left(-4\right).\left(-5\right)\right]^3=20^3\)